2023
DOI: 10.1186/s12872-023-03047-8
|View full text |Cite
|
Sign up to set email alerts
|

MetfOrmin BenefIts Lower Extremities with Intermittent Claudication (MOBILE IC): randomized clinical trial protocol

Abstract: Background Peripheral artery disease (PAD) affects over 230 million people worldwide and is due to systemic atherosclerosis with etiology linked to chronic inflammation, hypertension, and smoking status. PAD is associated with walking impairment and mobility loss as well as a high prevalence of coronary and cerebrovascular disease. Intermittent claudication (IC) is the classic presenting symptom for PAD, although many patients are asymptomatic or have atypical presentations. Few effective medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…A prospective study that enrolled 100 T2DM subjects with PAD after a 12-month follow-up showed the effectiveness of metformin in reducing adverse limb events, suggesting the usefulness of the drug in these patients [ 125 ]. Therefore, to determine whether metformin can play a role in symptomatic PAD, regardless of antidiabetic action, a prospective study, compared to placebo, is ongoing in non-diabetic subjects with intermittent claudication, called “Metformin BenefIts Lower Extremities with Intermittent Claudication” (MOBILE IC trial) [ 126 ]. The expected date for a first analysis of the results has been set for 2026 [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…A prospective study that enrolled 100 T2DM subjects with PAD after a 12-month follow-up showed the effectiveness of metformin in reducing adverse limb events, suggesting the usefulness of the drug in these patients [ 125 ]. Therefore, to determine whether metformin can play a role in symptomatic PAD, regardless of antidiabetic action, a prospective study, compared to placebo, is ongoing in non-diabetic subjects with intermittent claudication, called “Metformin BenefIts Lower Extremities with Intermittent Claudication” (MOBILE IC trial) [ 126 ]. The expected date for a first analysis of the results has been set for 2026 [ 108 ].…”
Section: Resultsmentioning
confidence: 99%